FDR and the Jews - Breitman, Richard, 1947-; Lichtman, Allan J. (The Belknap Press of Harvard University Press, 2013)
"In an extensive examination of this impassioned debate, Richard Breitman and Allan J. Lichtman find that the president was neither savior nor bystander. In "FDR and the Jews," they draw upon many new primary sources to offer an intriguing portrait of a consummate politician--compassionate but also pragmatic--struggling with opposing priorities under perilous conditions."--Provided by publisher.